(untitled) (INTERNATIONAL CONFERENCE OF NATURAL AND SOCIAL-HUMANITARIAN SCIENCES, 2024)
The article explores the various verbal and non-verbal cues employed in English to express mental states. It discusses how linguistic elements like tone, choice of words, and speech patterns convey emotions and thoughts. Additionally, it delves into non-verbal signals such as facial expressions, body posture, and eye movements that supplement verbal communication.